IMPLEMENTASI KEGIATAN SPIRITUAL JOURNEY DALAM PEMBENTUKAN KARAKTER RELIGIUS DAN MANDIRI SISWA KELAS XI SMA MUHAMMADIYAH 10 GKB GRESIK - Mahsun Mahsun; Ulyatun Nikmah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Character Education is an effort to encourage students to grow and develop the competence to think about and adhere to moral principles in their lives and to have the courage to do the right thing even when faced with various challenges. Character education is the process of transforming life values to be developed in a person's personality so that they become integrated into that person's life behavior. Therefore, character education is a process of internalizing or instilling positive values in students so that they have good character in accordance with the values referred to in both religion, culture, and the philosophy of the nation. In this research, it was related to the implementation of the Spiritual Journey Activities carried out at SMA Muhammadiyah 10 GKB Gresik towards the process of forming the religious and independent character of XI graders. Spiritual Journey is one of the excellent programs owned by SMA Muhammadiyah 10 GKB Gresik in the area of habituation and strengthening students' character through outdoor learning. The research method used in this study is qualitative research with a case study approach. The results of this study showed that the implementation of Spiritual Journey activities for XI graders of SMA Muhammadiyah 10 GKB Gresik had a good influence on the formation of religious and independent character for XI graders of SMA Muhammadiyah 10 GKB Gresik. This can be seen from the results of interviews with students, teachers, and parents. This activity can be developed for the better as a form of improving the quality of education services by collaborating with Muhammadiyah organizations in the wider area outside Gresik. The characters that are developed are religiosity and independence, and they must be monitored and evaluated for the personal development of students at school so that they can become better individuals.